Ampa Co’i Ndai: Local Understanding of Kafā’a in Marriage among Eastern Indonesian Muslims - Atun Wardatun (Al-Jami'ah Research Centre, 2016)
This article draws on an ethnographic research that focuses on the cultural practice of female-paid matrimonial funding, ampa co’i ndai (ACN), among semi-urban Bimanese Muslims of Eastern Indonesia. The practice takes place when the bride, with the help of her parents and female relatives, pays her marriage payment (co’i, including mahr). It is used only when the prospective groom is a government employee, for it is assumed as a social status raiser. During the declaration of marriage, the payment is announced to have come from the groom. This article uses the practice as a site to examine the particularity of practising Islamic laws in everyday life of eastern Indonesian Muslims. The narratives of nineteen Muslim women who have been involved in ACN reveal what its functions as an equalising mechanism, through which gendered power-relations is minimised while perpetuating traditional position of wives and husbands as a complementary couple within their family as well as before society. I argue that ACN has been seen as a modified understanding of kafā’a in fiqh which means “equality” to “complementarity.” However, this local understanding of kafā’a is a testament to the complexities of gender power relations.[Artikel ini adalah penelitian etnografi tentang praktik AMPA co’i ndai (ACN) di kalangan masyarakat semi-urban muslim Bima di kawasan timur Indonesia. Budaya ini dilaksanakan dengan cara pengantin perempuan, dengan bantuan orang tua dan saudara perempuannya, menyediakan biaya pernikahan (co’i dan mahar). Tradisi ini dipraktikkan hanya ketika calon pengantin pria adalah pegawai negeri, yang diasumsikan memiliki status sosial yang lebih. Namun, saat resepsi pernikahan, deiumumkan bahwa biaya-biaya berasal dari pengantin pria. Narasi kehidupan dari sembilan belas perempuan yang terlibat mengungkapkan fungsi ACN sebagai mekanisme penyetaraan gender dengan meminimalkan relasi kuasa serta nmendudukkan pasangan untuk saling melengkapi dalam keluarga maupun masyarakat. Praktik ACN dapat dilihat sebagai bentuk lokal pemahaman konsep kafā’a, yang berarti “kesetaraan” untuk “melengkapi”. Namun, pemahaman lokal kafā’a ini merupakan bukti kompleksitas relasi kuasa dalam masalah gender.]